Superabsorbent polymers to mitigate plastic drying shrinkage in a cement paste as studied by NMR. (October 2018) - Snoeck, D.; Pel, L.; De Belie, N.
Abstract: At early ages, a problem of plastic shrinkage can arise when a cement paste is subjected to harsh drying conditions during hardening. SuperAbsorbent Polymers (SAPs) are a promising admixture to mitigate shrinkage in cement pastes. By introducing internal curing by means of the stored mixing water in the SAPs, the plastic shrinkage can be partially mitigated, next to the mitigation of autogenous shrinkage during setting of the cement paste. The kinetics of water release by the SAPs towards the cementitious matrix have been studied in detail to understand the mechanism. Nuclear Magnetic Resonance (NMR) is an effective technique to non-destructively monitor the effects induced by the SAPs during this plastic period and hardening as a function of time. The SAPs are able to protect the cement paste internally from the harsh ambient drying conditions and are able to sustain the internal relative humidity. The plastic settlement was reduced and there was less plastic shrinkage measured. Below 5 mm of the surface in SAP specimens, the specimens were hardening as if put in sealed conditions.